Working towards dengue as a vaccine-preventable disease: challenges and opportunities. (3rd October 2017) - Shrivastava, Ambuj; Tripathi, Nagesh K; Dash, Paban K.; Parida, Manmohan
ABSTRACT: Introduction : Dengue is an emerging viral disease that affects the human population around the globe. Recent advancements in dengue virus research have opened new avenues for the development of vaccines against dengue. The development of a vaccine against dengue is a challenging task because any of the four serotypes of dengue viruses can cause disease. The development of a dengue vaccine aims to provide balanced protection against all the serotypes. Several dengue vaccine candidates are in the developmental stages such as inactivated, live attenuated, recombinant subunit, and plasmid DNA vaccines. Area covered : The authors provide an overview of the progress made in the development of much needed dengue vaccines. The authors include their expert opinion and their perspectives for future developments. Expert opinion : Human trials of a live attenuated tetravalent chimeric vaccine have clearly demonstrated its potential as a dengue vaccine. Other vaccine candidate molecules such as DENVax, a recombinant chimeric vaccine andTetraVax, are at different stages of development at this time. The authors believe that the novel strategies for testing and improving the immune response of vaccine candidates in humans will eventually lead to the development of a successful dengue vaccine in future.